(untitled) - J D Tracey-White (Rome, 1995)
There are 7 chapters in thic book. Chaper 1 sets the framework by considering different types of rural and urban retail markets, how they operate, thei likely physical and institutional deficiencies and benefits that might be expected if these defects are remedied. Chapter 3 outlines a practical methodology to undertake rapid and cost-effective surveys to understand how the present retail marketing system operates and how it may be improved. Chapter 4 and 5 are concerned with detailed design, including the preparation of market master plans, the zoning of specialised activities in the market, trafic circulation patterns, amarket's relationship to adjacent uses and potential conflicts. Chapter 7 provides an outline of the management and institutional factors which need to be taken into account when developing proposals for a new market or for upgrading existing market facilities, including the application of market regulations.
Keywords: food market